Report from the BIT’s 1st Annual World Congress of Biomedical Engineering Held in Xi’an, China, 9–11 November 2017 - Gerhard Litscher; Xiaodan Mei (Medicines, 2017)
We are delighted to present within this meeting report the abstracts of the “BIT’s 1st World Congress of Biomedical Engineering 2017” which has been hold in Xi’an in China [...]